Initiation of hemodialysis at one month following fistulogram in patients with advanced kidney disease. (April 2023) - Wilson, Eelin; Sacknovitz, Yoni; Dalmia, Varun; Sanon, Omar; Hatch, Ayesha; Dauer, Marc; Scher, Larry; Lipsitz, Evan; Koleilat, Issam
Objective: Previous studies have demonstrated that low contrast volume used in access-related interventions had limited effects on the progression of chronic kidney disease (CKD) after fistulography, but studies are limited and heterogeneous. We sought to evaluate the rate of and factors associated with progression to dialysis (HD) within 1 month after fistulography for patients with advanced CKD. Methods: A single-institution retrospective cohort analysis of patients with CKD stage IV and V, not yet on HD, undergoing fistulography from 1 January 2014 to 31 December 2018 was performed. The primary outcome was progression to HD within 1 month. Additional variables and the association with the primary outcome such as medical comorbidities, contrast type or volume were assessed. Results: A total of 34 patients underwent 41 fistulograms prior to HD initiation. Progression to HD within 1 month of fistulogram occurred in seven patients (all CKD V). The mean time between fistulogram and HD was 271 days for 31 of 34 patients who ultimately progressed to HD. Those with CKD IV began HD in 549 days on average, while those with CKD V began HD in 190 days on average. Three patients had not initiated HD at a mean of 539 days of follow-up. The only factors associated with progression to HD within 1 month included use of isovue ( p = .005) and elevated contrast volume, with a mean of 40 mL ( p = .027). Conclusion: Although none of the patients with CKD IV required HD within 1 month after fistulogram, the use of larger iodinated contrast volume was associated with progression to HD within 1 month of fistulography for patients with CKD V. Further studies should investigate the safety of iodinated and alternative (e.g., carbon dioxide) contrast media in fistulography or duplex-based HD access procedures for CKD patients, especially CKD V, not yet on HD.